Survey of beanfly (Ophiomyia spp) in Kabale District - Karamura, E.B. (International Center for Tropical Agriculture, 1991)
meanfly (Ophiomyia spp.) incidence was investigated at the farm field level to determine losses at successive plant ages over varying altitudes in the Kabale District of Uganda. A higher beanfly population was found at the 1,860-2,110 m altitude range than at both lower and higher ranges. Both beanfly species were found, but the dominant species was O. spencerella. Future research will analyze for crop loss due to beanfly damage and sampling dates will be increased to determine the onset of beanfly infestation. (AS)